Dietary acculturation and body composition changes in Division I female international student-athletes - Weerasekara, H. R.; de Souza, L.; Funderburk, L. (International Journal of Exercise Science Conference Proceedings, 2026)
Athletic performance relies on optimal body composition that supports biomechanics and bioenergetics of sport. Limited research exists on dietary acculturation and body composition changes in Division I female international student-athletes.